An Opportunity for Values Education in Higher Education: Social Responsibility and Healthy Living Course - Gökhan Izgar (Institute of Advanced Engineering and Science, 2018)
The purpose of this study is to determine the contribution of the “social responsibility and healthy living” course, which was put into effect at a state university for the first time in Turkey, within the scope of elective courses on students’ acquisition of values. The data in this study, in which action research, one of the qualitative research designs, was conducted, were obtained using the semi-structured interview form prepared by the researcher. The data obtained were analyzed using the descriptive analysis and content analysis techniques, which are qualitative data analysis methods. 39 students participated in the study on a voluntary basis. As a result of the analysis of the data, it was concluded that the action plan developed within the scope of the social responsibility and healthy living course was effective in the acquisition of values of taking responsibility, charitableness, being useful, ethics, empathy, importance of the institution of family, cooperation-solidarity, patience, gratitude (thankfulness), freedom of thought and respect for differences. Likewise, some of the students stated that this course contributed to their views and behaviors concerning healthy living. However, a considerable number of students were of the opinion that either the course did not make a contribution or made a partial contribution. In addition, the students pointed out that the way the course was taught was fruitful and practice-based,, that it was fun and informative and that the projects and readings contributed to learning. Yet, there were also negative student views about the course content and the method of teaching employed. Moreover, it was important that a theme emerged indicating that class hours were not sufficient.